Association of habitual alcohol use on risk-taking behaviors while using a car: The Korean National Health and Nutrition Examination Survey 2009–2013. (September 2020) - Lee, Doo Woong; Kim, Kwanghyun; Baek, Jongmin; Oh, Sarah Soyeon; Jang, Sung-In; Park, Eun-Cheol
Highlights: Alcohol use was related to risk-taking behavior while using a car among Koreans. This association was stronger in men, youth, and dwellers in higher incidence of traffic accident. The association was also strongest for driving under the influence of alcohol. An evidence of association between habitual drinking and risk behaviors which possibly lead to traffic accidents was seen. Abstract: Background: Using the Alcohol Use Disorders Identification Test-Korean revised version (AUDIT-KR), we examined the association between habitual alcohol use and risk-taking behaviors among car users. Methods: We used the data of 15, 043 car users aged 20 years or older from the Korea National Health and Nutrition Examination Survey (KNHANES) conducted between 2009 and 2013. Multivariable logistic regression analysis was used to investigate the associations between alcohol use and risk-taking behaviors (i.e., driving under the influence of alcohol, riding in a car being driven under the influence, not wearing a seat belt while driving, not wearing a seat belt in the passenger seat), while adjusting for individual-level covariates. Results: Compared to low-risk drinkers, high-risk drinkers (adjusted odds ratio [Adj.OR] 2.18, 95 % CI 1.96–2.42) and intermediate-risk drinkers (Adj.OR 1.39, 95 % CI 1.26–1.54) had higher odds of risk-taking behaviors while using a car. Stratifying by sociodemographic variables (i.e., sex, age, and region) led to differences in the relationship between alcohol-drinking level and risk-taking behaviors. Furthermore, alcohol-drinking level had significant positive associations with most of risk-taking behaviors, especially driving under the influence of alcohol and using a car with a drunken driver. Conclusion: Car users with high levels of alcohol consumption are more likely to be involved in risk-taking behaviors, especially in driving under the influence of alcohol. While causal relations cannot be established due to the nature of the cross-sectional design, it is possible that individuals' habitual alcohol consumption level can influence their risk-taking behaviors while using a car.